Pelaksanaan Terapi Bekam Kering pada Penderita Kolesterolemia - Syokumawena, Syokumawena; Sulistini, Rumentalia; Mediarti, Devi (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2022)
The incidence of dyslipidemia has a number that is not small, it needs proper monitoring and management so as not to cause severe problems or complications in the community. Service is carried out to increase cadre knowledge and provide opportunities for the community to get cupping therapy in lowering cholesterol levels. Cadres and 35 people who have cholesterolemia are present in community service activities. Activities are carried out in the Working Area of puskesmas and Integrated construction posts (Posbindu). As a result of this activity cadres gain knowledge about how to check cholesterol and the community gets cupping therapy. This activity should be sustainable so that it can improve the quality of life of the community.